Efforts to Reduce River Water Discharge through Land Use Control (Case Study: Upstream Ciliwung Watershed, Indonesia) - Shamira Nathania; Endrawati Fatimah; Benny B Suharto (Journal of Applied Geospatial Information, 2022)
Land-use change is the main cause of high runoff compared to other factors. The type of land use also plays a role in determining the amount of runoff that occurs. The Upstream Ciliwung watershed is blamed as the main causes of the flood disaster in Jakarta, the capital city. The land use in the upper stream has changed and causes increasing of run off to be higher than the capacity of river to drain it. This study aims to explore the land use changes of the Upstream Ciliwung Watershed from 1996 to 2016 and their consequences on the stream run off. Furthermore, the study also recommends the efforts needed to reduce river water discharge. The land use changes are identified by using spatial analysis method. The calculation of run off uses the rational method. Average rainfall data for every ten years is calculated by use of Gumbell distribution formula. The study shows that in the period 1996 – 2016, there was a change in land use in the upstream Ciliwung watershed. The area that continues to decline includes primary forest, open land, paddy fields, shrubs, and mixed gardens, all of which are categorized as undeveloped areas. The runoff discharge from 1996 – 2016 has increased from 278.77 to 465.57 mm/second that indicate runoff discharge is already in the Standby I position. Efforts that need to be made to reduce runoff water flow in the Ciliwung watershed are: 1) consistently develop and control land use change in the area based on the Jabodetabekpunjur Spatial Planning 2) consistently apply the building coverage ratio (BCR) regulation; 3) construct engineering and technology approach such as build infiltration wells in settlement, 4) forest rehabilitation and 5) conducting law enforcement.